Transaction Costs in the Preparation of Scientific Publications - V. Ya. Gelman (Ekonomika Nauki)
Preparation of scientific publications includes transaction costs as an integral part. The aim of the work was to analyze the changes over the past 50 years in transaction costs in the publication process and the impact of these costs on the results of publication activities. The article discusses the changes that have taken place in the procedure for choosing a publishing house, methods of the manuscript design, translation of the text, compiling a list of references, interaction with publishers and other issues of preparing scientific publications. It is shown that the reduction of transaction costs is one of the most important ways to increase the scientific and publication activity of teachers and researchers.